half(0) -> 0

half(s(s(

log(s(0)) -> 0

log(s(s(

TRS

↳Removing Redundant Rules

Removing the following rules from

log(s(0)) -> 0

where the Polynomial interpretation:

was used.

_{ }^{ }POL(0)= 0 _{ }^{ }_{ }^{ }POL(log(x)_{1})= 1 + x _{1}_{ }^{ }_{ }^{ }POL(s(x)_{1})= x _{1}_{ }^{ }_{ }^{ }POL(half(x)_{1})= x _{1}_{ }^{ }

Not all Rules of

TRS

↳RRRPolo

→TRS2

↳Removing Redundant Rules

Removing the following rules from

half(s(s(x))) -> s(half(x))

where the Polynomial interpretation:

was used.

_{ }^{ }POL(0)= 0 _{ }^{ }_{ }^{ }POL(log(x)_{1})= x _{1}_{ }^{ }_{ }^{ }POL(s(x)_{1})= 1 + x _{1}_{ }^{ }_{ }^{ }POL(half(x)_{1})= x _{1}_{ }^{ }

Not all Rules of

TRS

↳RRRPolo

→TRS2

↳RRRPolo

→TRS3

↳Removing Redundant Rules

Removing the following rules from

log(s(s(x))) -> s(log(s(half(x))))

where the Polynomial interpretation:

was used.

_{ }^{ }POL(0)= 0 _{ }^{ }_{ }^{ }POL(log(x)_{1})= 2·x _{1}_{ }^{ }_{ }^{ }POL(s(x)_{1})= 1 + x _{1}_{ }^{ }_{ }^{ }POL(half(x)_{1})= x _{1}_{ }^{ }

Not all Rules of

TRS

↳RRRPolo

→TRS2

↳RRRPolo

→TRS3

↳RRRPolo

...

→TRS4

↳Removing Redundant Rules

Removing the following rules from

half(0) -> 0

where the Polynomial interpretation:

was used.

_{ }^{ }POL(0)= 0 _{ }^{ }_{ }^{ }POL(half(x)_{1})= 1 + x _{1}_{ }^{ }

All Rules of

TRS

↳RRRPolo

→TRS2

↳RRRPolo

→TRS3

↳RRRPolo

...

→TRS5

↳Dependency Pair Analysis

Duration:

0:00 minutes